Limiting values of the one-bond C[sbnd]H spin-spin coupling constants of the imidazole ring of histidine at high-pH - Vila, Jorge Alberto (2017)
Assessment of the relative amounts of the forms of the imidazole ring of Histidine (His), namely the protonated (H+) and the tautomeric Nε2-H and Nδ1-H forms, respectively, is a challenging task in NMR spectroscopy. Indeed, their determination by direct observation of the 15N and 13C chemical shifts or the one-bond C[sbnd]H, 1JCH, Spin-Spin Coupling Constants (SSCC) requires knowledge of the “canonical” limiting values of these forms in which each one is present to the extent of 100%. In particular, at high-pH, an accurate determination of these “canonical” limiting values, at which the tautomeric forms of His coexist, is an elusive problem in NMR spectroscopy. Among different NMR-based approaches to treat this problem, we focus here on the computation, at the DFT level of theory, of the high-pH limiting value for the 1JCH SSCC of the imidazole ring of His. Solvent effects were considered by using the polarizable continuum model approach. The results of this computation suggest, first, that the value of 1JCε1H = 205 ± 1.0 Hz should be adopted as the canonical high-pH limiting value for this SSCC; second, the variation of 1JCε1H SSCC during tautomeric changes is minor, i.e., within ±1 Hz; and, finally, the value of 1JCδ2H SSCC upon tautomeric changes is large (15 Hz) indicating that, at high-pH or for non-protonated His at any pH, the tautomeric fractions of the imidazole ring of His can be predicted accurately as a function of the observed value of 1JCδ2H SSCC.